Integrated analysis of energy and water supply in islands. Case study of S. Vicente, Cape Verde. (1st December 2015) - Segurado, R.; Costa, M.; Duić, N.; Carvalho, M.G.
Abstract: The electricity production in S. Vicente is based on fossil fuel and wind power and, although there are significant wind resources, they are not fully used because of its intermittent nature. In a previous work, we proposed solutions to tackle this issue. Since this island does not have fresh water available, excess wind power can be provided to desalination units to produce desalinated water to supply the population. Other solution studied previously was the use of desalinated water in a pumped hydro system to store the remaining excess wind power. In this article, the scenarios modelled previously are updated with more recent data on energy and water consumption and the respective annual costs are estimated. The results show that with the current installed wind power and desalination capacity, and with the installation of a pumped hydro system, it is possible to have, by 2020, 36% of electricity production from renewable energy sources, with costs 7% lower than those forecasted for that year. If the installation of more wind power and desalination capacity is considered, renewable energy sources production can reach 72% (51% wind power, 21% pumped hydro), with about 19% decrease of costs in relation to those predicted for 2020. Highlights: Increase the integration of wind power by coupling the energy and water supply systems. Find solutions that minimize the costs while increasing the integration of wind. RES production can reach 72% of total electricity production. 19% of costs reduction and 49% decrease in CO2 emissions are achievable.